Biostimulants in bioconversion compost of organic waste: A novel booster in sustainable agriculture. (15th October 2021) - Huang, Shan; Zheng, Xin; Luo, Lingxun; Ni, Yuemin; Yao, Longren; Ni, Wuzhong
Abstract: Bioconversion technology has paved the way for solving the contradiction between population growth, food production reduction, and global environmental degradation because of its ability to convert organic waste into high-value products (including plant biostimulants) and stabilize organic materials. However, the current literature review and reference framework of biostimulants in bioconversion compost of organic waste have not yet surfaced. With the great advantages of bioconversion technology, this review focuses on combing and summarizing the biostimulants components (represented by betaines, chitin, humic substances, protein hydrolysates, and beneficial microorganisms) in bioconversion compost (larvae bioconversion compost and vermicompost) and their agricultural application. In addition, the complexity of the action mode of plant biostimulants produced in bioconversion compost, as well as the existing knowledge gaps, challenges, and opportunities, were also discussed in order to give full play to the potential and agricultural application value of bioconversion technology in the future. Graphical abstract: Image 1 Highlights: Bioconversion is an efficient process for richening plant biostimulants in compost. Betaines, chitin, humic substances and protein hydrolysates represent main biostimulants in bioconversion compost. Biostimulants in bioconversion compost and their application in sustainable agriculture were summarized. Research gaps, challenges and opportunities were prospected.